DEMOCRATIC TRADITIONS AND NEW MODELS OF DEMOCRACY - Gaspardo, Murilo [UNESP] (Univ Fed Pernambuco, 2015)
In a context in which Brazilian shows consolidated democracy, but whose functioning of its institutions is a matter of great discontent of the population, the demand for a reform of the political system established by the 1988 Constitution grows. However, proper treatment of this issue requires a reflection about the very concept of democracy in the face of profound changes undergone by the state and all forms of social organization. This article aims to make a contribution to this debate through a review of values, principles and traditional forms of democracy, as well as an analysis about new democratic models that can contribute to the enrichment of proposals for political reform.
Keywords: Democratic principles; Models of democracy; Democratic theory